O cálculo mental para ensinar: uma análise dos trabalhos elaborados por Maria do Carmo Santos Domite, 1980-1995 - Conceicao, Antonio Robert Chagas [UNIFESP] (2020)
This research is linked to thematic project A MATEMÁTICA NA FORMAÇÃO DE PROFESSORES E NO ENSINO: processos e dinâmicas de produção de um saber profissional, 1890-1990, and the purpose of this research is to analyse the mental calculus systematized by Maria do Carmo Santos Domite for the teacher training in the period from 1980 to 1995. Thus, the initial point of the time frame is the year that Domite started working at the São Paulo Municipal Education Secretariat and its limit refers to the year of publication of the last file regarding the mental calculus analyzed in this research. The primary sources of this research were the Memorial Acadêmico by Maria do Carmo Domite; Curso de Matemática por correspondência (1988); the article Cálculo mental (1989); and the text Cálculo Mental (1995). The analysis of the sources was guided by theoretical contribution that consider the professional knowledge of the teacher as a central theme of training and teaching, like Hofstetter, Schneuwly e Freymond (2017), Hofstetter e Schneuwly (2017), Bertini, Morais e Valente (2017). Based on the analyzes, were identified guidelines to the teacher for the teaching of mental calculus systematized by Domite, who understood the explanation of the oral solution by the student followed by the written systematization of the adopted strategies, process, that could take place using representations involving an explanatory scheme from unconventional groupings, as adding the equals, decomposing and conveniently associating and, relating a parcel to a “round number”. Using these procedures, the development of the student's mental calculus skills was expected by the teacher and, at the same time, providing the contact with the properties of the decimal numbering system. A theoretical elaboration of these guidelines allowed this research to characterize the mental calculus systematized by Domite as a tool for the teacher's work, that is, a mental calculus for teach the decimal numbering system in times when it was advocated in favor of teaching with understanding by concrete experiences.